Usage of academic libraries: the role of service quality, resources, and user characteristics - Simmonds, Patience L.; Andaleeb, Syed Saad (© Graduate School of Library and Information Science. University of Illinois at Urbana-Champaign, 2016)
This is an Open Access Article. It is published by Library Trends ,Measuring Service Quality and the definite version is available at: http://hdl.handle.net/2142/8368